Strategi Komunikasi Organisasi Kantor Kementerian Agama Provinsi Sumatera Utara Dalam Mensosialisasikan Nilai-Nilai Moderasi Beragama di MAN 2 Model Medan - Shanti Amalia (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2026)
"Moderation" derives from the word "moderate," signifying an absence of excess or the maintenance of a middle ground. When paired with "religious," the term "religious moderation" refers to a religious stance that eschews violence and avoids extremism in religious practice. Religious moderation represents a perspective and practice that emphasizes balance, tolerance, and respect for diversity within society. While rapid social change, globalization, and intense intercultural interaction can enrich societal dynamics, they also harbor the potential for conflict if the values of pluralism are not managed wisely. The Indonesian government, through the Ministry of Religious Affairs under the leadership of Lukman Hakim Saifuddin, established religious moderation as a national agenda starting in 2019. Consequently, this study aims to elucidate the organizational communication strategy employed by the North Sumatra Provincial Office of the Ministry of Religious Affairs to disseminate the values of religious moderation at MAN 2 Model Medan. This study employs a descriptive method with a qualitative approach to describe and explain real-world situations based on existing facts. Data collection techniques included interviews, observation, and documentation conducted by the researcher at the study site. Based on the findings regarding the North Sumatra Provincial Ministry of Religious Affairs' organizational communication strategy for promoting religious moderation values at MAN 2 Model Medan, it can be concluded that the strategy was implemented systematically, incorporating the five communication components proposed by Carl I. Hovland: communicator, message, media, communicant (audience), and effect.